African Americans have a lower prevalence of portal vein thrombosis at the time of liver transplantation. Issue 7 (July 2017) - Bezinover, Dmitri; Reeder, Ethan; Aziz, Faisal; Saner, Fuat; McQuillan, Patrick; Kadry, Zakiyah; Riley, Thomas; Guvakov, Dmitri; Janicki, Piotr K.
Abstract: Background: Perioperative vascular thrombotic events in patients undergoing liver transplantation (LT) are associated with significant morbidity and mortality. Methods: In this retrospective UNOS database analysis, we evaluated the prevalence of portal vein thrombosis (PVT) and factors contributing to PVT development in different ethnic groups. Results: Of the 47 953 LT performed between 2002 and 2015, we identified 3642 cases of PVT. African Americans (AA) had a significantly lower prevalence of PVT compared to other ethnic groups (p = 0.0001). Multivariable regression analysis confirmed that AA were less likely than other ethnicities to have PVT (OR = 0.6). AA cohort was more likely to have infectious or autoimmune causes of liver failure (OR = 1.6, 1.7 respectively) as well as higher creatinine and INR compared to other groups (OR = 1.6, 1.3 respectively). AA's were less likely to have encephalopathy, ascites, or variceal bleeding, which might indicate lower portal pressures. AA's were listed for LT later than other ethnicities and had both a lower functional status and higher MELD score at the time of registration. Discussion: AA's had a significantly lower prevalence of preoperative PVT despite having a greater number of factors predisposing to thrombosis. This predisposition should be considered before instituting perioperative antithrombotic therapy.